The Effectiveness of High School Affirmations (ADEM) Repatriation: Empirical Evidence from Central Java and Special Region of Yogyakarta, Indonesia - Trisno Martono; Baedhowi Baedhowi; Hery Sawiji; Salman Alfarisy Totalia; Budi Wahyono; Dini Octoria; Sigit Wahyudi; Dowes Ardinugroho; Erna Gesti Fadrusiana (BIRCU, 2020)
The ADEM repatriation program is one of the government's commitments to address the education problems of children of Indonesian migrant workers (TKI) abroad who have difficulty obtaining access to education services. This study aims to determine the effectiveness of the implementation of the Repatriation ADEM program in the provinces of Central Java and Yogyakarta Special Region. This study uses primary data obtained from questionnaires and interviews. The research sample consisted of four secondary schools (one school in DIY and three schools in Central Java). The results showed thatThe existence of the ADEM Repatriation program is a government policy that is quite effective in overcoming the education problems of children of Indonesian migrant workers (TKI) who have difficulty obtaining access to education services. However, in some areas the implementation is not optimal, both in management management, learning implementation, and monitoring and evaluation.